Newspaper Censorship in China: Evidence from Tunneling Scandals - Hope, Ole-Kristian; Li, Yi; Liu, Qiliang; Wu, Han (Management Science, 2021)
Media dissemination plays an important role in facilitating price discovery. Political pressure that restricts media dissemination can hinder this function and affect investors’ perceptions. This paper studies the magnitude of newspaper censorship in China and its economic consequences using a setting of tunneling scandals. We find significant evidence of censorship of tunneling-related negative news at the national and local levels. We further show that news that survives censorship reduces information asymmetry and improves pricing efficiency. Censorship blocks informative tunneling news and delays incorporation of tunneling reporting into prices. This paper was accepted by Brian Bushee, accounting.